Immediate and Short-term Outcome of Acute Disseminated Encephalomyelitis (ADEM) after corticosteroid therapy - Mahbub, Mustafa; Sarker, Shaoli; Mozumder, Suraj C (Northern International Medical College Journal, 2021)
Background : Acute disseminated encephalomyelitis (ADEM) is an acute demyelinating disorder of the central nervous system (CNS) occurring predominantly but not exclusively in children. The presence of severe disturbance of consciousness together with multifocal neurological symptoms and signs especially in a child under 10 years of age; favours a diagnosis of ADEM. Neuroimaging is essential investigation for establishing the diagnosis of ADEM. High-dose steroid treatment frequently results in a dramatic clinical improvement. Objective: This study aimed to describe our experience with Acute Disseminated Encephalomyelitis (ADEM) focusing on the clinical features, neuroimaging, and outcome after treatment with high-dose steroid. Method: This retrospective observational study was conducted in children who were admitted as inpatients in Paediatric Neurosciences Department of Dhaka Shishu Hospital (DSH) with the diagnosis of ADEM during the period of 2017- 2019. All patients got high dose IV methylprednisolone for 5 days followed by 2 weeks tapering dose of steroid. Outcome was observed on the 7th day of treatment and 6 months after discharge from hospital. Result: A total of 16 patients who were diagnosed as ADEM were included in this study. Twelve children (75%) had a recent upper respiratory tract illness. Patients presented most often with motor deficits (88%) and secondly with altered consciousness (63% ) followed by seizure ( 50% ). MRI brain was the preferable neuroimaging which mostly (41.7%) showed multifocal symmetrical demyelination patch. On the 7th day of steroid treatment, significant improvement in motor function and level of consciousness occurred (p values were 0.001% and 0.014% respectively). After 6 months of discharge from hospital; no motor deficit, age-appropriate cognitive level and no seizure in 71%, 57% and 71% respectively. Conclusion: High dose corticosteroid treatment in ADEM is significantly effective in improvement of motor impairment and consciousness level on immediate follow up. Northern International Medical College Journal Vol.11 (2) Jan 2020: 468-470